A block copolymer-based composite protective layer with ion channels and a preparation method and application thereof
Patent Information
- Application Number
- CN202611076695.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-20
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]然而,金属锌负极界面界面失衡问题是制约其产业化的核心瓶颈,电解液体系内锌离子主要以水合络合形态存在,剥离配位水分子所需能量较高,造成锌金属沉积分布不均,持续生长的锌枝晶极易刺破隔膜,造成电池内部短路失效;锌金属在水环境中还会自发发生腐蚀、析氢副反应,持续生成氧化锌、氢氧化锌等惰性绝缘副产物,不断恶化电极界面阻抗,造成电池容量快速衰减、库伦效率持续下降;同时电极-电解液界面会生成空间电荷层,增加锌离子迁移阻力,直接削弱电池快充、高倍率放电性能
本发明首次将具有柔性机械性能的嵌段共聚物与具有刚性有序离子通道的离子型共价有机框架复合,嵌段共聚物基体赋予了保护层优异的机械强度和柔韧性,能够适应锌负极循环过程中的体积变化并物理抑制枝晶生长;离子型共价有机框架纳米片则提供了高速的锌离子传输“离子通道”。该复合保护层中离子型共价有机框架的离子通道内带负电的磺酸基团能与锌离子产生强离子偶极相互作用,加速锌离子传输并诱导其优先沿(002)晶面致密沉积。
Smart Images

Figure CN122889681A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of zinc-ion batteries, and more particularly to a block copolymer-based composite protective layer with ion channels, its preparation method, and its application. Background Technology
[0002] The ongoing global energy structure upgrade, the iteration of portable electronic devices, and the construction of large-scale energy storage power stations have led to a surge in demand for safe, low-cost, and high-capacity energy storage devices. Aqueous zinc-based ion batteries, leveraging the abundant reserves of metallic zinc, outstanding theoretical specific capacity, and low reduction potential, have become a highly promising next-generation energy storage technology. Furthermore, when paired with aqueous electrolytes that pose no risk of open flame or explosion, they effectively compensate for the high cost of lithium-ion batteries and the flammability and explosiveness of organic electrolytes, making them a novel energy storage system with significant industrialization potential.
[0003] However, the imbalance at the zinc anode interface is a core bottleneck restricting its industrialization. Zinc ions in the electrolyte system mainly exist in a hydrated complex form, and the energy required to strip the coordinated water molecules is high, resulting in uneven zinc metal deposition. The continuously growing zinc dendrites can easily puncture the separator, causing internal short circuit failure of the battery. In an aqueous environment, zinc metal will also spontaneously undergo corrosion and hydrogen evolution side reactions, continuously generating inert insulating byproducts such as zinc oxide and zinc hydroxide, which continuously worsen the electrode interface impedance, causing rapid capacity decay and continuous decline in coulombic efficiency. At the same time, a space charge layer will be generated at the electrode-electrolyte interface, increasing the resistance to zinc ion migration and directly weakening the battery's fast charging and high-rate discharge performance.
[0004] Among various zinc anode modification schemes, surface-constructed protective layers are the mainstream approach to improve interface stability. However, existing protective coatings all have uncompromising shortcomings: traditional polymer coatings (PVDF, polyethylene glycol, etc.) have weak mechanical properties and insufficient ion conductivity, are prone to cracking and peeling off from the zinc substrate during charge-discharge cycles, and are difficult to effectively block electrolyte erosion and dendrite propagation, nor can they optimize zinc ion desolvation kinetics; inorganic ceramic coatings (zinc fluoride, alumina, etc.) have high hardness but are obviously brittle, have poor adhesion to the zinc substrate, and gaps are easily formed between the coating and the metal, allowing dendrites to penetrate along the gaps. At the same time, the ion conductivity is low and cannot be adapted to high-current charge-discharge conditions.
[0005] Covalent organic frameworks (COFs) are considered ideal materials for anode interface modification layers due to their regular and interconnected pores, modifiable functional groups, and excellent mechanical rigidity. However, existing COF-based protective layer preparation processes have significant shortcomings for industrialization: mainstream solvothermal synthesis requires a high-temperature, high-pressure, and closed environment, with a reaction cycle lasting several days, resulting in high energy consumption and cumbersome procedures; coating formation largely relies on binders, leading to poor film uniformity and weak adhesion at the electrode interface; most COF materials lack directional zinc ion-affinity active sites, making it difficult to balance and control zinc ion flux and reduce desolvation resistance, and still pose a risk of dendrite precipitation, resulting in low overall preparation efficiency and unsuitability for mass production.
[0006] Existing zinc anode protective layers can only slightly extend battery cycle life. After charging and discharging, the zinc deposition layer still exhibits an uneven morphology, making it difficult to simultaneously achieve the triple effects of suppressing dendrites, blocking corrosion hydrogen evolution side reactions, and accelerating zinc ion desolvation. There is still huge room for improvement in the long-cycle stability and capacity retention of aqueous zinc-ion batteries.
[0007] Therefore, the industry urgently needs to develop a composite protective layer with mild preparation conditions, a simple process, and a tight bond between the coating and the zinc substrate. This layer should also possess multiple properties such as excellent ion conductivity, directional regulation of zinc deposition, and accelerated desolvation, thereby fundamentally suppressing zinc dendrite formation, corrosion, and hydrogen evolution side reactions, and comprehensively improving the cycle life and capacity maintenance of aqueous zinc-ion batteries. Summary of the Invention
[0008] To overcome the technical defects in the prior art, the present invention provides a method for preparing and applying a block copolymer-based composite protective layer with ion channels.
[0009] To achieve the above objectives, the present invention provides the following technical solution: First aspect: A method for preparing a block copolymer-based composite protective layer with ion channels includes the following steps: S1. Ionic covalent organic framework nanosheets are synthesized by polymerization of multifunctional aldehyde monomers and multifunctional amine monomers containing zinc-philic functional groups. S2. The ion-covalent organic framework nanosheets described in step S1 are subjected to ion exchange treatment with metal ion salts to obtain a functionalized ion-covalent organic framework nanosheet dispersion. S3. Dissolve the block copolymer in a mixed solvent to obtain the block copolymer solution; S4. Mix the ionic covalent organic framework dispersion with the block copolymer solution evenly to obtain a casting solution; S5. The casting solution is coated onto the zinc surface to obtain a block copolymer-based composite protective layer with ion channels.
[0010] In some embodiments, the method for preparing the block copolymer-based composite protective layer with ion channels, wherein step S1 satisfies at least one of the following conditions: The molar ratio of the multifunctional aldehyde monomer and the multifunctional amine monomer containing zinc-philic functional groups is 1:(1~2). The polymerization reaction is a polymerization reaction that can form a two-dimensional porous structure; The polymerization reaction takes 2-5 days; The polymerization reaction includes: preparing the multifunctional aldehyde monomer into an organic phase, preparing the multifunctional amine monomer containing zinc-philic functional groups into an aqueous phase, and adding the organic phase dropwise onto the aqueous phase for interfacial polymerization.
[0011] In some embodiments, the method for preparing the block copolymer-based composite protective layer with ion channels, wherein the multifunctional aldehyde monomer is an aromatic compound containing two or more aldehyde groups; The polyfunctional amine monomer containing zinc-philic functional groups is an aromatic compound containing two or more amino groups and having sulfonic acid, carboxyl, or amide groups.
[0012] In some embodiments, the method for preparing the block copolymer-based composite protective layer with ion channels, wherein the aromatic compound containing two or more aldehyde groups is selected from any one of 1,3,5-tricarboxyloylphloroglucinol, 1,3,5-benzenetricarboxaldehyde, and 2,4,6-tricarboxypyridine; The aromatic diamine monomer containing a sulfonic acid group is selected from any one of 2,5-diaminobenzenesulfonic acid, 3,5-diaminobenzenesulfonic acid, 4,6-diamino-1,3-benzenedisulfonic acid, 2,4-diaminobenzenesulfonic acid, and 4,4'-diaminobiphenyl-2,2'-disulfonic acid.
[0013] In some embodiments, the method for preparing the block copolymer-based composite protective layer with ion channels, step S2 satisfies at least one of the following conditions: The metal ion salt includes one or more of acetate, nitrate, and sulfate; The ion exchange temperature is 30~100℃; The ion exchange reaction time is 1 to 7 days; The concentration of the dispersion is 0.5~1wt%.
[0014] In some embodiments, the method for preparing the block copolymer-based composite protective layer with ion channels, wherein the block copolymer in step S3 includes polyether, polyester, polyamide, polyurethane, and polyetheramide block copolymer; Preferably, the polyether amide block copolymer includes any one of polyamide 6-polyoxyethylene block copolymer, polyamide 11-polyoxyethylene block copolymer, and polyamide 12-polyoxyethylene block copolymer; The concentration of the polymer solution is 5-10 wt%.
[0015] In some embodiments, in the method for preparing the block copolymer-based composite protective layer with ion channels, the volume ratio of the ion-covalent organic framework material to the block copolymer in the casting solution in step S4 is 1 to (0.5:3). The mixing time is 10-15 hours.
[0016] The present invention also provides a block copolymer-based composite protective layer with ion channels, which is prepared by the above-described method for preparing a block copolymer-based composite protective layer with ion channels.
[0017] The present invention also provides a block copolymer-based composite protective layer with ion channels, which is used to improve the cycle stability of aqueous zinc-ion batteries, suppress zinc dendrite growth, and regulate the orientation of zinc ion deposition.
[0018] The present invention also provides an aqueous zinc-ion battery, comprising the above-mentioned block copolymer-based composite protective layer with ion channels, an ion covalent organic framework, and an artificial solid electrolyte interface layer.
[0019] The second aspect: This invention has discovered that by ion exchange treatment, metal ions (preferably Li) with good coordination ability can be introduced into the pores of ion-covalent organic framework nanosheets. + These metal ions can not only bind to sulfonic acid groups (-SO3) on the ionic covalent organic framework. - The zinc-loving functional groups (such as sulfonic acid groups) form a stable coordination environment and can interact with polar groups (such as ether oxygen bonds) in the block copolymer matrix after subsequent coating and film formation, forming uniformly distributed metal-organic complex sites. More importantly, the sulfonic acid groups on the inner wall of the ionic covalent organic framework pores are negatively charged, which has a positive effect on Zn. 2+ These sulfonic acid groups exhibit strong affinity for Li introduced through ion exchange. + Together, they create a highly efficient ion transport channel within the composite protective layer: the negatively charged sulfonic acid groups attract and accelerate Zn. 2+ The migration of Zn and the repulsion of anions simultaneously inhibit hydrogen evolution side reactions; while the uniformly distributed metal-organic complex sites within the pores act as Zn... 2+ Preferred nucleation centers for deposition can induce Zn 2+Uniform and dense deposition on the negative electrode surface effectively avoids dendrite formation caused by the "point effect." Simultaneously, the composite of block copolymers and ion-covalent organic framework nanosheets significantly enhances the mechanical strength and flexibility of the protective layer, further strengthening the functional groups within the ion channels for Zn. 2+ The regulatory effect of solvation structure can effectively reduce Zn 2+ The deposited overpotential synergistically inhibits the growth of zinc dendrites. Through the above mechanism, the block copolymer-based composite protective layer with ion channels prepared in this invention can significantly improve the cycle stability and rate performance of the zinc anode.
[0020] The aqueous zinc-ion battery provided by this invention includes a zinc anode modified with the aforementioned block copolymer-based composite protective layer having ion channels. This protective layer is prepared using a drop casting method. The modified electrode is subjected to temperature variations at 25°C and 1 mA cm⁻¹. -2 1 mAh cm -2 Under symmetrical conditions, the battery cycled for more than 4,000 hours (bare zinc only about 180 hours), which is significantly better than bare zinc and pure polymer protective layer.
[0021] Compared with the prior art, the present invention has the following beneficial effects: This invention is the first to combine a block copolymer with flexible mechanical properties with an ionic covalent organic framework with rigid, ordered ion channels. The block copolymer matrix endows the protective layer with excellent mechanical strength and flexibility, enabling it to adapt to volume changes during zinc anode cycling and physically suppress dendrite growth. The ionic covalent organic framework nanosheets provide high-speed zinc ion transport "ion channels." In this composite protective layer, the negatively charged sulfonic acid groups within the ion channels of the ionic covalent organic framework can generate strong ion dipole interactions with zinc ions, accelerating zinc ion transport and inducing its preferential dense deposition along the (002) crystal plane.
[0022] After cycling, the zinc anode with the protective layer of this invention exhibits a (002) / (100) crystal plane strength ratio that can be increased to four times the initial value, forming a layered and dense deposition morphology, fundamentally suppressing dendrite formation. Benefiting from the rapid desolvation process and optimized zinc ion migration kinetics, the protective layer of this invention significantly improves battery performance: at 1 mA cm⁻¹... -2 At current densities of 5 mA cm⁻¹, the modified zinc anode can achieve an ultra-long cycle life of over 4000 hours; at 5 mA cm⁻¹ -2 It can still cycle stably for nearly 3000 hours at high current densities; when applied to full cells, it can achieve stable cycling at 2 A g. -1 After 2000 cycles at a current density, the capacity retention rate is still as high as 89%.
[0023] The present invention has a simple process and a wide range of raw material selection, providing a variety of optional aldehyde monomers, amino monomers, metal ion salts and block copolymers. Through optimal combination, a high-performance composite protective layer can be obtained, which has good technical universality and industrial application prospects. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0025] Figure 1 Photograph of the zinc anode (10) with block copolymer-based composite protective layer and ion channel prepared in Example 1 of the present invention.
[0026] Figure 2 This is a scanning electron microscope image of the surface of the zinc anode (10) with ion channels prepared in Example 1 of the present invention, which is a block copolymer-based composite protective layer.
[0027] Figure 3 The image shows a focused ion beam scanning electron microscope (FSE) image of the cross section of the zinc anode (10) modified with a block copolymer-based composite protective layer with ion channels prepared in Example 1 of this invention, which shows the thickness of the interface layer and its adhesion to the zinc substrate.
[0028] Figure 4 The zinc anode (10) modified with a block copolymer-based composite protective layer having ion channels, prepared in Example 1 of this invention, was tested at 1 mA cm⁻¹. -2 1 mAh cm -2 The surface scanning electron microscope image after 60 hours of cycling under the specified conditions shows a uniform and dense zinc deposition layer.
[0029] Figure 5 The symmetrical cells assembled from the zinc anode (10) with ion channel-modified block copolymer-based composite protective layer prepared in Example 1, the zinc anode (20) with ion channel-modified block copolymer-based composite protective layer prepared in Example 2, and the zinc anode (30) with ion channel-modified block copolymer-based composite protective layer prepared in Example 3, at 1 mA cm⁻¹ -2 1 mAh cm -2 Comparison of cyclic performance under different conditions.
[0030] Figure 6Symmetric cells assembled from the bare zinc anode (40) of Example 1, the zinc anode (50) modified with an ion-covalent organic framework block copolymer-based composite protective layer, and the zinc anode (60) modified with a block copolymer layer of Comparative Example 3, were used at 1 mA cm⁻¹. -2 1mAh cm -2 Comparison of cyclic performance under different conditions.
[0031] Figure 7 The zinc anode (10) modified with a block copolymer-based composite protective layer with ion channels prepared in Example 1 of this invention and the bare zinc anode (40) of Comparative Example 1 were compared at 1 mA cm⁻¹. -2 1 mAh cm -2 Digital images after 60 hours of cycling under certain conditions.
[0032] Figure 8 The full cell assembled with the zinc anode (10) of Example 1 of the present invention having a block copolymer-based composite protective layer with ion channels and the full cell assembled with the bare zinc anode (40) of Comparative Example 1 were compared at 1 A g. -1 Comparison of long-cycle performance under current density. Detailed Implementation
[0033] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0034] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all purchased commercially and used directly without any special treatment.
[0035] Unless otherwise specified, the analytical methods in the embodiments all adopt conventional instrument or equipment settings and conventional analytical methods.
[0036] Example 1 Commercially available 0.15 mmol of 2,5-diaminobenzenesulfonic acid was ultrasonically dissolved in 30 mL of deionized water to form an aqueous phase; 0.1 mmol of 1,3,5-tricarboxymethylphloroglucinol was ultrasonically dissolved in 20 mL of n-octanoic acid to form an organic phase. The organic phase was slowly added dropwise to the aqueous phase and allowed to stand at room temperature for 3 days to carry out interfacial polymerization. The lower aqueous dispersion was collected and dialyzed for 3 days to obtain an ionovalent organic framework (H). + A dispersion of (type) nanosheets was prepared. Lithium acetate was added to the dispersion to a final volume of 1 M, and the mixture was stirred at 60°C for 3 days. The mixture was then dialyzed again for 3 days to obtain Li. +An ion-covalent organic framework nanosheet dispersion with a concentration of approximately 0.5 wt% was prepared. A 5 wt% polymer solution was prepared by dissolving a polyether amide block copolymer (PA6 / PEO) in ethanol / water (70 / 30 wt%). The ion-covalent organic framework dispersion and the polymer solution were mixed at a volume ratio of 1:1 and stirred for 12 h to obtain a casting solution. The casting solution was then applied using a drop-casting method at 85 μL / cm² intervals. -2 The proportions were uniformly coated onto a 15 mm diameter circular zinc plate. Using a solvent evaporation phase inversion method, the plate was placed in a well-ventilated and dry place at room temperature for 12 h to obtain a zinc anode modified with a block copolymer-based composite protective layer containing ion channels (10). The sample image is shown below. Figure 1 As shown, the surface scanning electron microscope image is as follows: Figure 2 As shown, the cross-sectional FIB-SEM image is as follows. Figure 3 As shown.
[0037] Example 2 Commercially available 0.15 mmol of 2,5-diaminobenzenesulfonic acid was ultrasonically dissolved in 30 mL of deionized water to form an aqueous phase; 0.1 mmol of 1,3,5-tricarboxymethylphloroglucinol was ultrasonically dissolved in 20 mL of n-octanoic acid to form an organic phase. The organic phase was slowly added dropwise to the aqueous phase and allowed to stand at room temperature for 3 days to carry out interfacial polymerization. The lower aqueous dispersion was collected and dialyzed for 3 days to obtain an ionovalent organic framework (H). + A dispersion of (type) nanosheets was prepared. Lithium acetate was added to the dispersion to a final volume of 1 M, and the mixture was stirred at 60°C for 3 days. The mixture was then dialyzed again for 3 days to obtain Li. + An ion-covalent organic framework nanosheet dispersion with a concentration of approximately 0.5 wt% was prepared. A 5 wt% polymer solution was prepared by dissolving a polyether amide block copolymer (PA6 / PEO) in ethanol / water (70 / 30 wt%). The ion-covalent organic framework dispersion and the polymer solution were mixed at a volume ratio of 2:1 and stirred for 12 h to obtain a casting solution. The casting solution was then applied using a drop-casting method at 85 μL / cm² intervals. -2 The proportion of the coating was uniformly applied to a circular zinc plate with a diameter of 15 mm. The zinc anode modified with a block copolymer-based composite protective layer with ion channels was obtained by using the solvent evaporation phase inversion method and placing it in a ventilated and dry place at room temperature for 12 h.
[0038] Example 3 Commercially available 0.15 mmol of 2,5-diaminobenzenesulfonic acid was ultrasonically dissolved in 30 mL of deionized water to form an aqueous phase; 0.1 mmol of 1,3,5-tricarboxymethylphloroglucinol was ultrasonically dissolved in 20 mL of n-octanoic acid to form an organic phase. The organic phase was slowly added dropwise to the aqueous phase and allowed to stand at room temperature for 3 days to carry out interfacial polymerization. The lower aqueous dispersion was collected and dialyzed for 3 days to obtain an ionovalent organic framework (H).+ A dispersion of (type) nanosheets was prepared. Lithium acetate was added to the dispersion to a final volume of 1 M, and the mixture was stirred at 60°C for 3 days. The mixture was then dialyzed again for 3 days to obtain Li. + An ion-covalent organic framework nanosheet dispersion with a concentration of approximately 0.5 wt% was prepared. A 5 wt% polymer solution was prepared by dissolving a polyether amide block copolymer (PA6 / PEO) in ethanol / water (70 / 30 wt%). The ion-covalent organic framework dispersion and the polymer solution were mixed at a volume ratio of 1:2 and stirred for 12 h to obtain a casting solution. The casting solution was then applied using a drop-casting method at 85 μL / cm² intervals. -2 The proportion of the coating was uniformly applied to a circular zinc plate with a diameter of 15 mm. The zinc anode (30) was obtained by placing it in a ventilated and dry place at room temperature for 12 h using a solvent evaporation phase inversion method and having an ion channel block copolymer-based composite protective layer modified.
[0039] Comparative Example 1 The pretreated zinc foil (pretreatment method is the same as in Example 1) was used directly without any coating modification to obtain a bare zinc negative electrode (40). Compared with Example 1, Comparative Example 1 omitted the coating modification.
[0040] Comparative Example 2 Commercially available 0.15 mmol of 2,5-diaminobenzenesulfonic acid was ultrasonically dissolved in 30 mL of deionized water to form an aqueous phase; 0.1 mmol of 1,3,5-tricarboxymethylphloroglucinol was ultrasonically dissolved in 20 mL of n-octanoic acid to form an organic phase. The organic phase was slowly added dropwise to the aqueous phase and allowed to stand at room temperature for 3 days to carry out interfacial polymerization. The lower aqueous dispersion was collected and dialyzed for 3 days to obtain an ionovalent organic framework (H). + A nanosheet dispersion (type 1) was prepared. This dispersion was used directly in subsequent reactions without ion exchange treatment. The above ion-covalent organic framework dispersion was mixed with the polymer solution at a volume ratio of 1:1 and stirred for 12 h to obtain a casting solution. The casting solution was then applied using a drop-casting method at a rate of 85 μL / cm². -2 The mixture was uniformly coated onto a 15 mm diameter circular zinc plate. Using a solvent evaporation phase inversion method, the plate was placed in a well-ventilated and dry place at room temperature for 12 h to obtain a zinc anode (50) modified with an ion-covalent organic framework block copolymer-based composite protective layer. In Comparative Example 1, the ion exchange treatment step was omitted compared to Example 1.
[0041] Comparative Example 3 Polyether amide block copolymer (PA6 / PEO) was dissolved in ethanol / water (70 / 30 wt%) to prepare a 5 wt% polymer solution, which was then used to prepare a casting solution. The casting solution was applied using a drop-casting method at a rate of 85 μL / cm². -2The proportions were uniformly coated onto a 15 mm diameter circular zinc plate. Using a solvent evaporation phase inversion method, the plate was placed in a ventilated and dry place at room temperature for 12 h to obtain a zinc anode modified with a block copolymer layer (60). In Comparative Example 2, compared to Example 1, no ionic covalent organic framework nanosheet dispersion was added to the casting solution; only a pure polyether amide block copolymer solution was used to prepare the protective layer.
[0042] Application examples The zinc anodes prepared in the examples and comparative examples were assembled into Zn-Zn symmetrical cells using a 2032 battery case: The assembly process of the Zn-Zn symmetrical cell is as follows: anode case, spring, gasket, zinc anode covered with protective film, glass fiber separator, zinc anode covered with protective film, and positive electrode case. The electrolyte is a 3 M Zn(OTf)2 aqueous solution.
[0043] Example 1 (Comparison of Cycle Performance of Zn-Zn Symmetrical Batteries) The test results are shown in Table 1.
[0044] Table 1 Comparison of Cycle Performance of Zn-Zn Symmetric Cells
[0045] Depend on Figure 3 As can be seen, the focused ion beam scanning electron microscope image of the cross section of the zinc anode (10) modified with the block copolymer-based composite protective layer with ion channels prepared in Example 1 of the present invention shows the thickness of the interface layer and its adhesion to the zinc substrate.
[0046] Depend on Figure 4 As shown in Table 1, the zinc anode (10) modified with a block copolymer-based composite protective layer having ion channels prepared in Example 1 of this invention exhibits a performance at 1 mA cm⁻¹. -2 1 mAh cm -2 The surface scanning electron microscope image after 60 hours of cycling under the specified conditions shows a uniform and dense zinc deposition layer.
[0047] From Table 1 and Figure 5 It can be seen that the zinc anode (10) modified with the block copolymer-based composite protective layer with ion channels prepared in Example 1 is assembled into a Zn-Zn symmetric cell. At 25°C, 1 mA cm⁻¹ -2 (1 mAh cm) -2 The performance of the protective film was tested under the following conditions. After 80 hours of cycling, the scanning electron microscope image of the zinc anode surface coated with the block copolymer-based composite protective layer with ion channels in Example 1 is shown below. Figure 4 As shown, the zinc deposition layer has a more uniform and dense surface with a simple morphology, exhibiting uniform and dense zinc ion deposition behavior, which is beneficial for the long-term cycling of the zinc anode. At 25℃ and 1 mA cm⁻¹ -2 (1 mAh cm)-2 Its cycling performance was tested under the following conditions. After 40,000 hours of cycling, its symmetrical cell remained stable with an overpotential of about 50 mV.
[0048] From Table 1 and Figure 5 It can be seen that the zinc anode (20) modified with the block copolymer-based composite protective layer with ion channels prepared in Example 2 can be assembled into a Zn-Zn symmetric cell. At 25°C, 1 mA cm⁻¹ -2 (1 mAh cm) -2 Under the conditions tested, its cycle stability was lower than that of Example 1 (results are as follows). Figure 5 (As shown).
[0049] From Table 1 and Figure 5 It can be seen that the zinc anode (30) modified with the block copolymer-based composite protective layer with ion channels prepared in Example 3 was assembled into a Zn-Zn symmetric battery. Under the same conditions, its cycle stability was lower than that of Example 1.
[0050] like Figure 6 As shown, the bare zinc anode (40) prepared in Comparative Example 1 was assembled into a Zn-Zn symmetrical cell. Under the same conditions, after approximately 180 hours of cycling, the cell experienced a short circuit and severe overpotential fluctuations, as shown in the results. Figure 6 As shown, the scanning electron microscope image of the zinc plate surface after 60 hours of cycling is as follows. Figure 7 As shown, a large number of irregular flaky dendrites appear on the surface.
[0051] From Table 1 and Figure 6 It can be seen that the zinc anode (50) modified with the ionic covalent organic framework block copolymer-based composite protective layer prepared in Comparative Example 2 was assembled into a Zn-Zn symmetric battery. Under the same conditions, the battery short-circuited after about 1800 hours of cycling, and the overpotential fluctuated violently.
[0052] From Table 1 and Figure 6 It can be seen that the zinc anode (60) modified with the block copolymer layer prepared in Comparative Example 3 was assembled into a Zn-Zn symmetric cell. Under the same conditions, the polarization increased significantly and failed after about 1100 hours of cycling.
[0053] As can be seen from Table 1, from Figure 7 It can be seen that the zinc anode (10) with ion channel block copolymer-based composite protective layer modified with ion channel prepared in Example 1 of the present invention and the bare zinc anode (40) of Comparative Example 1 are compared at 1 mA cm⁻¹. -2 1 mAh cm -2 Digital images obtained after 60 hours of cycling under the specified conditions, where Comparative Example 1 showed severe surface corrosion, while Example 1 showed less surface corrosion.
[0054] As can be seen from Table 1, from Figure 8It can be seen that the full cell assembled with the zinc anode (10) with the block copolymer-based composite protective layer of the ion channel in Example 1 of the present invention and the full cell assembled with the bare zinc anode (40) in Comparative Example 1 are comparable in 1 A g. -1 The comparison graph of long-cycle performance at current density shows that Example 1 has a capacity retention of 80% and a coulombic efficiency of 99% after 4000 cycles.
[0055] Example 2 (Zn-V2O5 full cell test) The test results are shown in Table 2.
[0056] Table 2 Comparison of long-cycle performance of Zn-V2O5 full cells
[0057] The assembly process of the Zn-V2O5 full cell is as follows: negative electrode shell, spring sheet, gasket, zinc negative electrode (10) modified with a block copolymer-based composite protective layer with ion channels prepared in Example 1, glass fiber separator, and V2O5 positive electrode (active material loading of 0.68 mg cm⁻¹). -2 The electrode shell and electrolyte were 3 M Zn(OTf)2 aqueous solution. Cyclic performance tests were conducted at 25°C with a current density of 2 A g. -1 The voltage range is 0.3~1.6 V. The results are as follows: Figure 8 As shown in Figure 1 and Table 2.
[0058] The full battery still retains approximately 178 mAh g after 4000 cycles. -1 The specific capacity was high, with a capacity retention of up to 89% and an average coulombic efficiency of 99%. In contrast, a full cell (Zn||V₂O₅) assembled using the bare zinc anode (40) of Comparative Example 1, under the same conditions, exhibited a capacity retention of only 72% after 4000 cycles. Furthermore, at 1 A g… -1 At the current density, the PC@Zn‖V2O5 full cell retains 80% of its capacity after 4000 cycles.
[0059] The above results indicate that the block copolymer-based composite protective layer with ion channels provided by the present invention can significantly improve the cycle stability of aqueous zinc-ion full batteries.
[0060] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a block copolymer-based composite protective layer with ion channels, characterized in that, Includes the following steps: S1. Ionic covalent organic framework nanosheets are synthesized by polymerization of multifunctional aldehyde monomers and multifunctional amine monomers containing zinc-philic functional groups. S2. The ion-covalent organic framework nanosheets described in step S1 are subjected to ion exchange treatment with metal ion salts to obtain a functionalized ion-covalent organic framework nanosheet dispersion. S3. Dissolve the block copolymer in a mixed solvent to obtain the block copolymer solution; S4. Mix the ionic covalent organic framework dispersion with the block copolymer solution evenly to obtain a casting solution; S5. The casting solution is coated onto the zinc surface to obtain a block copolymer-based composite protective layer with ion channels.
2. The method for preparing the block copolymer-based composite protective layer with ion channels according to claim 1, characterized in that, Step S1 satisfies at least one of the following conditions: The molar ratio of the multifunctional aldehyde monomer and the multifunctional amine monomer containing zinc-philic functional groups is 1:(1~2). The polymerization reaction is a polymerization reaction that can form a two-dimensional porous structure; The polymerization reaction takes 2-5 days; The polymerization reaction includes: preparing the multifunctional aldehyde monomer into an organic phase, preparing the multifunctional amine monomer containing zinc-philic functional groups into an aqueous phase, and adding the organic phase dropwise onto the aqueous phase for interfacial polymerization.
3. The method for preparing the block copolymer-based composite protective layer with ion channels according to claim 1, characterized in that, The multifunctional aldehyde monomers are aromatic compounds containing two or more aldehyde groups; The multifunctional amine monomer containing zinc-philic functional groups is an aromatic compound containing two or more amino groups and having sulfonic acid, carboxyl, or amide groups.
4. The method for preparing the block copolymer-based composite protective layer with ion channels according to claim 3, characterized in that, The aromatic compound containing two or more aldehyde groups is selected from any one of 1,3,5-tricarboxyloylphloroglucinol, 1,3,5-benzenetricarboxaldehyde, and 2,4,6-tricarboxyloylpyridine. The aromatic diamine monomer containing a sulfonic acid group is selected from any one of 2,5-diaminobenzenesulfonic acid, 3,5-diaminobenzenesulfonic acid, 4,6-diamino-1,3-benzenedisulfonic acid, 2,4-diaminobenzenesulfonic acid, and 4,4'-diaminobiphenyl-2,2'-disulfonic acid.
5. The method for preparing the block copolymer-based composite protective layer with ion channels according to claim 1, characterized in that, Step S2 satisfies at least one of the following conditions: The metal ion salt includes one or more of acetate, nitrate, and sulfate; The ion exchange temperature is 30~100℃; The ion exchange reaction time is 1 to 7 days; The concentration of the dispersion is 0.5~1wt%.
6. The method for preparing the block copolymer-based composite protective layer with ion channels according to claim 1, characterized in that, The block copolymers mentioned in step S3 include polyether, polyester, polyamide, polyurethane, and polyetheramide block copolymers; Preferably, the polyether amide block copolymer includes any one of polyamide 6-polyoxyethylene block copolymer, polyamide 11-polyoxyethylene block copolymer, and polyamide 12-polyoxyethylene block copolymer; The concentration of the polymer solution is 5-10 wt%.
7. The method for preparing the block copolymer-based composite protective layer with ion channels according to claim 1, characterized in that, In the casting solution described in step S4, the volume ratio of the ionic covalent organic framework material to the block copolymer is 1 to (0.5:3). The mixing time is 10-15 hours.
8. A block copolymer-based composite protective layer with ion channels, characterized in that, It is prepared by the method for preparing a block copolymer-based composite protective layer with ion channels as described in any one of claims 1 to 7.
9. The application of a block copolymer-based composite protective layer with ion channels as described in claim 8 in improving the cycle stability of aqueous zinc-ion batteries, inhibiting zinc dendrite growth, and regulating zinc ion deposition orientation.
10. An aqueous zinc-ion battery, characterized in that, It includes the block copolymer-based composite protective layer with ion channels, the ion covalent organic framework, and the artificial solid electrolyte interface layer as described in claim 8.